SEADFCON 2017 theme "Quality diabetes care beyond socio cultural barriers" - Maskey, R.; Gupta, P.P.; Kattel, V. (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
No Abstract available. Jour of Diab and Endo Assoc of Nepal 2017; 1(1): 1-2